2019
DOI: 10.2196/15738
|View full text |Cite
|
Sign up to set email alerts
|

Internet-Based Cognitive Behavioral Therapy via Videoconference for Patients With Bulimia Nervosa and Binge-Eating Disorder: Pilot Prospective Single-Arm Feasibility Trial

Abstract: BackgroundA major problem in providing mental health services is the lack of access to treatment, especially in remote areas. Thus far, no clinical studies have demonstrated the feasibility of internet-based cognitive behavioral therapy (ICBT) with real-time therapist support via videoconference for bulimia nervosa and binge-eating disorder in Japan.ObjectiveThe goal of the research was to evaluate the feasibility of ICBT via videoconference for patients with bulimia nervosa or binge-eating disorder.MethodsSev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…Most other studies identified by the search examined smaller single group samples for bulimia and related disorders, reporting reductions in bulimic symptoms (Abrahamssom, Ahlund, Ahrin, & Alfonsson, 2018 ; Hamatani et al, 2019 ; Simpson et al, 2006 ) and satisfaction with the online modality (Abrahamssom et al, 2018 ; Simpson et al, 2005 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most other studies identified by the search examined smaller single group samples for bulimia and related disorders, reporting reductions in bulimic symptoms (Abrahamssom, Ahlund, Ahrin, & Alfonsson, 2018 ; Hamatani et al, 2019 ; Simpson et al, 2006 ) and satisfaction with the online modality (Abrahamssom et al, 2018 ; Simpson et al, 2005 ).…”
Section: Resultsmentioning
confidence: 99%
“…Another approach to improve accessibility to CBT for individuals residing in remote areas is to utilize a videoconferencing system [18][19][20]. In comparison to ICBT, videoconference-delivered CBT (VCBT) has the advantage of enabling remote treatment through interactive real-time communication between the therapist and the patient, which makes it similar to face-to-face CBT.…”
Section: Videoconference-delivered Cbtmentioning
confidence: 99%
“…In part, this is because evidence-based treatments have been predicated largely on face-toface contact (e.g., monitoring risk; the weighing of patients- Waller & Mountford, 2015). There are some preliminary studies showing that telehealth can be beneficial in treating eating disorders and obesity (e.g., Abrahamsson, Ahlund, Ahrin, & Alfonsson, 2018; Byrne, Crosby, & Le Grange, 2017; Cassin et al, 2016;Giel et al, 2015;Hamatani et al, 2019;Sockalingam et al, 2017), but fewer substantial studies that support this approach (e.g., Ertelt et al, 2011;Mitchell et al, 2008). Kazdin, Fitzsimmons-Craft, and Wilfley (2017) have identified telehealth as requiring further study and development, though the limited evidence to date suggests we can deliver effective therapies for eating disorders at a distance with thoughtful planning and careful delivery (Sproch & Anderson, 2019).…”
Section: Introductionmentioning
confidence: 99%